Resistance to red-rot (Colletotrichum falcatum) in early-maturing crosses of sugarcane (Saccharum officinarum) - Singh, R K; Singh, Atul; Saxena, M M S; Singh, S B; Singh, G P (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during spring planting season of 1993--94 to study the inheritance of economic trails and resistance to red-rot (Colletotrichum falcatum Went) in early-maturing selections from crosses of sugarcane (Saccharum officinarum L.). Fourteen inter-varietal crosses were evaluated in the preliminary varietal trial (C3 stage). The crosses 'MS 68/47' x 'CoS 510', 'Co 740' x 'Co 775'. 'Co 1158' X 'CoS 510' and 'Co 1158' X 'Co 62198' proved belter for yielding elite early, high-sugared genotypes. The genotypes'S 2799/90', 'S 6699/90', 'S 7092/90' and'S 10609/89' were found promising for yield, sugar and red-rot resistance.